Low-Grade Inflammation as a Predictor of Antidepressant and Anti-Inflammatory Therapy Response in MDD Patients: A Systematic Review of the Literature in Combination With an Analysis of Experimental Data Collected in the EU-MOODINFLAME Consortium - Arteaga-Henríquez, Gara; Simon, Maria S.; Burger, Bianka; Weidinger, Elif; Wijkhuijs, Annemarie; Arolt, Volker; Birkenhager, Tom K.; Musil, Richard; Müller, Norbert; Drexhage, Hemmo A. (Frontiers in Psychiatry, 2019)
Low grade inflammation not only plays a role in the pathogenesis of major depressive disorder (MDD), but probably also in the poor responsiveness to regular antidepressants. There are also indications that anti-inflammatory agents improve the outcomes of antidepressants. Aim: To study whether the presence of low grade inflammation predicts the outcome of antidepressants, anti-inflammatory agents or combinations thereof. Methods: We carried out a systematic review of the literature on the prediction capability of the serum levels of inflammatory compounds and/or the inflammatory state of circulating leukocytes for the outcome of antidepressant/anti-inflammatory treatment in MDD. We compared outcomes of the review with original data (collected in two limited trials carried out in the EU project MOODINFLAME) on the prediction capability of the inflammatory state of monocytes (as measured by inflammatory gene expression) for the outcome of venlafaxine, imipramine or sertraline treatment, the latter with and without celecoxib added. Results: Collectively, the literature and original data showed that: 1. Raised serum levels of pro-inflammatory compounds (in particular of CRP/IL-6) characterize an inflammatory form of MDD with poor responsiveness to predominately serotonergic agents, but a better responsiveness to antidepressant regimens with a) (add-on) noradrenergic, dopaminergic or glutamatergic action or b) (add-on) anti-inflammatory agents such as infliximab, minocycline or eicosapentaenoic acid, showing - next to anti-inflammatory - dopaminergic or lipid corrective action. 2. These successful anti-inflammatory (add-on) agents, when used in patients with low serum levels of CRP/IL-6, decreased response rates in comparison to placebo. Add-on aspirin, in contrast, improved responsiveness in such “non-inflammatory” patients. 3. Patients with increased inflammatory gene expression in circulating leukocytes had a poor responsiveness to serotonergic/noradrenergic agents. Conclusions: The presence of inflammation in patients with MDD heralds a poor outcome of first line antidepressant therapies. Immediate step-ups to dopaminergic or glutamatergic regimens or to (add-on) anti-inflammatory agents are most likely indicated. However, at present, insufficient data exist to design protocols with reliable inflammation-parameter-cut-off points to guide such therapies, the more since detrimental outcomes are possible of anti-inflammatory agents in “non-inflamed” patients.